Mathematics Creative Thinking Skills in Problem-Based Learning Model Reviewed from Learners’ Curiosity and Gender - Arifin, Mustofa; Suyitno, Hardi; Dewi (Nino Adhi), Nuriana Rachmani (Universitas Negeri Semarang, 2020)
Creative thinking skills are important to be trained in mathematics learning because solving math problems cannot be separated from these skills. This research described learners’ mathematics creative thinking skills reviewed by curiosity and gender. This research is sequential explanatory research with a mixed methods with quantitative and qualitative approaches. Thirty-five learners of the 10th graders learning group were given a curiosity test to discover their curiosity types. They were stimulated by problem-based learning to develop their mathematics creative thinking skills. The findings showed that learners had various mathematics, creative thinking skills. They were proven by epistemic, perceptual curiosity, and perceptual curiosity diverse learners for both males and females. They were creative. The male learners with epistemic curiosity diverse categories were also creative while the female was very creative. Based on this research, the mathematical creative thinking ability of female gender students with the epistemic curiosity type is more dominant than perceptual curiosity.